Park characteristics and park use : factors influencing adolescents' use of Urban parks in Shiraz, Iran / Zohreh Mahdiar - Mahdiar, Zohreh (2015)
Parks offer a unique setting within an urban landscape, providing opportunities for physical activities, enjoyment of nature, social interactions, and escape. Despite the importance of parks, adolescents in Iran, who were regarded as the main users of parks in the past, are now more inclined to patronize other new modernized public spaces, such as shopping centers, which inevitably decrease their usage of parks. Therefore, this study aims to increase the knowledge of parks' socio-physical characteristics that are necessary to entice adolescents to use urban parks more often in Shiraz, Iran. A mixed-method approach was used in this study. The qualitative method, which was the semi-structured in-depth interviews with adolescents, was conducted to specifically explore the characteristics of parks that adolescents find important in their use of urban parks in the area of under studied. Another reason for use of the qualitative research was to develop the age and culturally appropriate measures for a survey that assesses park characteristics which influence the use of urban parks among adolescents in Shiraz. Two pilot studies were conducted to finalize the questionnaire for the face validity, construct validity, and the reliability of the instrument. The main survey was conducted to examine the link between perceived measures of park socio-physical characteristics and the use of urban parks by a population of adolescents, and investigate the determinant socio-physical characteristics of parks on park use in the present situation in Shiraz. Moreover, the issues of non-use of urban parks were identified by the respondents. A supplementary survey was conducted at the end of the study to quantitatively evaluate the importance of each socio-physical characteristics of parks for using urban parks from an adolescent's perspective. The results of qualitative study identified seven (7) socio-physical characteristics of parks (factors) that influence park use including: 1) accessibility; 2) recreational facilities; 3) recreational programs; 4) safety; 5) aesthetics & landscaping; 6) condition & maintenance; and 7) social environment. The results of the second pilot study and the EFA (exploratory factor analysis) reorganized the items and reduced the number of factors from 7 to 6, including 1) accessibility; 2) recreational facilities; 3) recreational programs; 4) safety; 5) aesthetics and condition; 6) social connectedness. The results of the main study showed that safety concerns, the presence of anti-social behaviour in parks, the presence of police advisors, and the lack of facilities were the most important obstacles to increased park use among adolescents in Shiraz. The examination of socio-physical characteristics of parks that impact the use of parks among adolescents revealed that the perception of accessibility of the park and social connectedness in park environment were associated with park use. Other perceived park characteristics include safety, programs, and aesthetics and condition showed weak correlation with park use. However, perceived provided facilities were not associated with park use. The results also showed that in the present situation, only the perception of accessibility and social connectedness in park environment is capable of predicting park use. The results also showed that all of the socio-physical characteristics of urban parks are lower than the adolescents' expectations. The conclusion of this study highlights the importance of perceived socio-physical characteristics of parks, including accessibility and social interaction in predicting adolescents' use of urban parks in Shiraz.